Efek Moderasi Financial Distress Pada Faktor Determinan Auditor Switching - Nanda, Mayang Setia; Wahyuni, Sri; Setyadi, Edi Joko; Inayati, Nur Isna (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
The importance of external auditor services causes auditor independence to be considered. Auditor independence can be maintained if a company conducts auditor switching. This research examine financial distress as a moderating influence of the previous year's audit opinion, management change, KAP reputation, and tenure audit on switching auditors. The research was conducted  on property and real estate  companies listed on the Indonesia Stock Exchange for 2020-2022. The sampling method used is purposive sampling so that the sample obtained is as many as 62 companies with a total of 186 data samples. The analysis showed that audit tenure is the only factor affecting auditor switching. In contrast, other factors such as the previous year's audit opinion, management changes, and KAP reputation do not influence switching auditors and financial distress variables or moderate all independent variables on switching auditors. The results of this study are expected  to contribute to the development of theory and can be useful for auditors to find out why companies to switch auditors.